The outbreak of COVID-19: Resilience and its predictors among parents of schoolchildren carrying out online learning in Indonesia - Abd Nasir (Elsevier, 2021)
Objective: Online learning during the COVID-19 outbreak, puts mental stress on parents and their children so that this requires extraordinary resilience when parents get additional tasks to accompany children in online learning that is done at home. The current study seeks to evaluate the resilience of parents accompanying schoolchildren in online learning. Besides, this study also examines independent socio-demographic predictors of parental resilience. Methods: This descriptive-analytic cross-sectional study was conducted on 392 parents of children participating in online learning at home. Data were collected through an online questionnaire survey in the provinces of Java and Bali. Demographic questionnaires and the Connor-Davidson Resilience Scale (CD-RISC) were used to collect data. Data were analyzed using descriptive statistics and regression analysis with p < 0.05. Results: Simultaneously the independent variables affect the resilience of parents as indicated by the value of F (9.010), p-value (0.000), and R (0.376). The predictors of parental resilience were the gender of the parents with the t-value (3.280), p-value (0.001), β (4.572), parent's employment status with the t-value (3.752), p-value (0.001), β (4,348), financial status with the t-value (4.754), p-value (0.000), β (5.087), and the gender of the children with the t-value (2.849), p-value (0.005), β (4.873). Conclusion: Predictor factors that affect the resilience of parents in providing online learning assistance during the COVID-19 pandemic need to get more serious attention, especially for mothers who have lower resilience than fathers. So that their children can still achieve better academic achievements